Thames Barrier design proceedings of the conference held in London on 5 October, 1977. (Institution of Civil Engineers, 1978)
The papers in this conference volume cover the background to the project, the geotechnical and environmental concerns, and all aspects of the design of the barrier, with particular reference to sector gates.